2022
DOI: 10.1002/adma.202201914
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Triggered Stiffening of Shape‐Memory Polyurethanes Composed of Hard Backbone Dangling PEG Soft Segments

Abstract: Shape‐memory polymers (SMPs) induced by heat or water are commonly used candidates for biomedical applications. Shape recovery inevitably leads to a dramatic decrease of Young's modulus due to the enhanced flexibility of polymer chains at the transition temperature. Herein, the principle of phase‐transition‐induced stiffening of shape‐memory metallic alloys (SMAs) is introduced to the design of molecular structures for shape‐memory polyurethane (SMPUs), featuring all‐hard segments composed of main chains that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 57 publications
2
23
0
Order By: Relevance
“…As a commercial material widely used in blood-contact fields, 52,53 Pellethane 2363-80AE (80AE) was used as a control. PEG is often used for surface modification to reduce the adhesion and activation of platelets for blood-contact materials, 54–56 thus PEG-based PU (PEGPU) was synthesized according to our reported method 14 as another control in our study (detailed information of PEGPU is shown in Table S4, ESI†). The results showed that the number of platelets adhered to the surface of TAPU1020 was slightly lower than that of 80AE.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a commercial material widely used in blood-contact fields, 52,53 Pellethane 2363-80AE (80AE) was used as a control. PEG is often used for surface modification to reduce the adhesion and activation of platelets for blood-contact materials, 54–56 thus PEG-based PU (PEGPU) was synthesized according to our reported method 14 as another control in our study (detailed information of PEGPU is shown in Table S4, ESI†). The results showed that the number of platelets adhered to the surface of TAPU1020 was slightly lower than that of 80AE.…”
Section: Resultsmentioning
confidence: 99%
“…Histocompatibility assessments were conducted according to the literature. 14 The detailed method is shown in the ESI †…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, athermal heating, which is possible by careful selection of the nanofillers incorporated in the polymer matrix, is a potentially viable means of exploiting the shape memory materials for remote actuation. The stimulus could be light 17 , ultrasound 18 , water 19 , microwaves 20 , etc. Magnetic stimulation is a potential means of remote actuation of these materials via indirect heating.…”
Section: Introductionmentioning
confidence: 99%
“…[23] On the other hand, the powerful capillary pressure created by water evaporation forces the skeleton to deform. [24] Furthermore, the hydration/dehydration of copolymer regulates the interchain binding forces (energy storage for shape recovery), [25] relieving/locking internal stresses. If the interchain binding can be controlled directionally by prestimulation, it is likely to obtain the activatable shape-memory property.…”
mentioning
confidence: 99%